Performans in gravitacija - Murnik, Maja (Amfiteater (Ljubljana), 2017)
The article discusses the increasing number of artworks "above the ground" (with an emphasis on performance art) that have been produced recently, focussing on several striking examples of art that strive to lift up off the ground: aerial theatre or teatro aereo (in Italian Futurism), space art, and the postgravity art of Dragan Živadinov. The examples are discussed in relation to three key issues crucial for the understanding of such art: (1) gravity, which is understood by these aerial (or space) artists not only as a fundamental force that establishes our place in the Earth's environment but also as a fatal force that obstructs the liberation of man, art and thinking. Humankind's ability to escape to the "open sky" (Virilio), establishes a different perception of space and a reorganisation of the view. This also implies (2) a transformation of the traditional notions of body and embodiment. Contrary to prevalent interpretations of aerial and space art that focus first and foremost on the description and interpretation of individual art projects, performances and visions, this article examines the issue of body from a philosophical perspective with the help of the extended notion of the body (Merleau-Ponty). The third issue discussed is (3) the question of scientific abstraction.
Keywords: Biomehanika Noordung; body art; gledališki projekti; gravitacija; gravity; performance art; postgravitacijska umetnost; postgravity art; space; vesolje; Živadinov, Dragan, 1960-